Employability of West Visayas State University Communication Graduates Philippines - Ian C Espada; Rona Dhel C. Alingasa; Shiela Mae Coronado Quero (Jurnal Studi Jurnalistik, 2023)
To cope with the demands of globalization, communication graduates must be provided with appropriate knowledge and skills needed in the industry. To find out how WVSU communication graduates perform in employment, this tracer study was conducted. This study looked into the employment profile of the Bachelor in Broadcasting, Bachelor in Journalism, and Bachelor of Science in Development Communication graduates of 2011-2013. It also traced the transition to employment of the graduates, their level of satisfaction towards the competencies acquired and the significance of the curriculum in the acquisition of knowledge and skills. This descriptive survey utilized a questionnaire adapted from the Graduate Tracer Study (GTS) instrument used by the Universities and Colleges in the Philippines. Findings revealed that most of the graduates are females, single, and permanently employed. Graduates considered their degree programs relevant to their jobs and they were satisfied with the knowledge and skill they acquired from their degrees. The result of the tracer study is a proof that the three curricular programs play a big role in the lives of the graduates especially in acquiring several skills and knowledge needed by a professional to compete in the challenging world of employment.